Five varsities among world's top one per cent - News Straits, Times (Sabah) (New Straits Times (Sabah), 2016)
MALACCA: Five Malaysian research universities have been listed in the world's top one per cent of best universities in the latest Quacquarelli Seymonds (QS) World University rankings of 2016/2017